The Analysis of Language Style Used by Characters in Cars Movie - Massing, Matthew Alexander Jovanca; Matradewi, Ni Ketut Widhiarcani; Aryani, I Gusti Agung Istri (IAI Nasional Laa Roiba Bogor, 2024)
Language style is the use of language based on speech relationships with listeners to communicate with the conditions experienced in social interaction. The analysis is based on the five language styles using Martin Joos' theory. Namely frozen style (oratorical style), formal style (deliberative style), consultative style, casual style and intimate style. This style of language can be identified through the situation when the speaker is speaking, whether formal or casual, public or private, who listens to us when we speak, whether it's our friends, parents, or strangers. Because the data in this study are film dialogues that are transcribed into textual form, the researcher uses a qualitative method where data is collected by watching movies then finding out conversations that contain language styles in communication, then classifying based on the types of language styles found in the film, then find the dominant type of language style.